(untitled) (Baltic Journal of Sport and Health Sciences, 2016)
Background. Existing research indicates that both teachers and prospective teachers who are physically active in comparison with inactive generally easier cope with physical and psychosocial problems. This topic, particularly psychosocial development of individuals and their participation in sports, has attracted the attention of researchers in recent years. There are a lot of studies on this issue, but less is known about the relationship between physical activity participation and psychological resilience. Therefore, the purpose of this study was to determine the association between experience of physical activity and psychological resilience of prospective teachers according to some variables. Methods. A sample of 331 last year student teachers (134 females and 197 males) who study at the Faculty of Education at Karadeniz Technical University in Northeast Turkey was evaluated. We used Childhood and Adolescence Physical Activity Levels Questionnaire to determine the physical activity experience. Besides, we applied the Brief Resilience scale to analyse the psychological resilience. The data was analysed by using the Pearson’s Correlation Coefficient, Simple Linear Regression and Independent Sample t-Test. Results. The research findings show that there was positive and significant relationship between psychological resilience and physical activity experience of prospective teachers. Regression analysis revealed that participation of physical activity was found to be significant predictors of resilience. In addition, both physical activity levels and resilience of prospective teachers with respect to gender, department and licensed sports participation status were found significant. Conclusions. Physical activity has numerous beneficial psychological effects. Furthermore, current research results suggest that experiences of physical activity play a role in psychological resilience of prospective teachers. It was also concluded that prospective teachers should be encouraged to participate in physical activity. The development of this aspect of the policy can contribute to psychological resilience of prospective teachers. Keywords: sport, psychological resilience, teacher education.